Radiological Heatmap of Tarsometatarsal Capsule Locations: A Cadaveric Study - Bedri Karaismailoglu MD; Matthias Peiffer MD; Fernando Raduan MD; Julian J. Hollander BSc; Ashley Knebel MS; John Kwon MD; Soheil Ashkani Esfahani MD; Christopher P. Miller MD (Foot & Ankle Orthopaedics, 2024)
Introduction/Purpose: Minimal invasive proximal metatarsal osteotomy (PMO) offers a successful approach for addressing metatarsus adductus while avoiding exposure of all metatarsals, thereby reducing the risk of complications such as wound infections and non-unions. An important hurdle is the absence of direct visualization for precise osteotomy placement. Staying within the tarsometatarsal (TMT) capsule enhances the chances of better union due to improved blood supply, although operating outside the capsule can aid in correcting more significant deformities. Despite having a macroscopic understanding of anatomical locations through specimens, there has been a lack of prior reports on their mapping in fluoroscopic images. Developing such maps could significantly improve the navigational skills of surgeons. This study aims to present heatmaps that illustrate the positions of distal attachments of TMT capsules. Methods: A total of nine specimens below the knee, devoid of any prior bone or joint abnormalities, were thawed a day prior to the experiments. After dissecting the dorsal skin, neurovascular structures, and tendons, only the bones and capsules remained. Flexible wires were placed alongside the distal edges of TMT capsules, encompassing the 1st, 2nd, 3rd, and 4th tarsometatarsal joints. This arrangement aimed to make the paths of these capsules visible when observed through X-ray imaging. The wires were then securely attached to the structures using a soft tissue adhesive. Fluoroscopy images were captured, including a calibration marker of a known diameter, in addition to taking macroscopic photographs. The specific coordinates of these structures were marked in a three-dimensional space within specialized 3D software. Subsequently, these coordinates were imported into a custom-designed Python script crafted for the purpose of generating heatmaps. Results: The heatmaps were successfully produced encompassing all TMT capsules spanning from the 1st to the 4th, and these were overlaid onto an anteroposterior fluoroscopy image of the foot (refer to Figure 1). This gradient of colors serves as a visual representation of differing magnitudes, with red denoting the most prevalent areas of the distal attachment of the TMT capsule, while blue corresponds to lower occurrences. Conclusion: These heatmaps not only showcase the predominantly observed sites of distal TMT attachments, depicted in red, but also signify diverse deviations, identifiable by the presence of less frequent zones indicated in blue. Consequently, surgeons are advised to consider these findings while planning their osteotomies based on their preferred positions. By furnishing surgeons with an extensive heatmap that outlines potential tarsometatarsal capsule insertions, this research not only furnishes them with a dependable guiding resource but also establishes a foundation for more assured and prosperous minimally invasive midfoot fusion procedures. Figure 1: The heatmap of 1st to 4th tarsometatarsal capsules on AP fluoroscopy.